Linking migration, HIV/AIDS and urban food security in Southern and Eastern Africa - Crush, Jonathan; Frayne, Bruce; Grant, Miriam (International Food Policy Research Institute, 2006)
This paper provides a review of the literature on migration, HIV/AIDS and urban food security, and attempts to draw the links between these three powerful dynamics which are at play in Southern and Eastern Africa. The aim of the paper is to stimulate discussion and provide a platform for developing an action research agenda to inform policy and programming within these three inter-connected sectors. This review demonstrates that migration, HIV/AIDS and urban food security interact in complex ways that are little researched and understood in the Southern and Eastern African context. To date research on urban food security has been concerned with urban systems of acquisition and production, with an emphasis on the informal sector and more recently on urban agriculture. Much less attention has been paid to linkages and food chains between rural and urban areas and the degree to which they are embedded within systems of migration. Recent studies from the Southern and Eastern Africa as well as West Africa show that where urban and rural links are strong, it is the resources associated with these connections that dominate urban households’ coping strategies, rather than the intra-urban household relationships suggested by the current literature on urban livelihoods amongst the poor. While urban to rural remittances has been the predominant direction of commodity and cash transfers, benefiting the rural household economy, this dynamic is changing, with direct food transfers from rural households to urban households on the rise, as part of the migration and urbanization processes.